2015
DOI: 10.3390/en81112358
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Quantum-Behaved Lightning Search Algorithm Approach to Improve the Fuzzy Logic Speed Controller for an Induction Motor Drive

Abstract: This paper presents a novel lightning search algorithm (LSA) using quantum mechanics theories to generate a quantum-inspired LSA (QLSA). The QLSA improves the searching of each step leader to obtain the best position for a projectile. To evaluate the reliability and efficiency of the proposed algorithm, the QLSA is tested using eighteen benchmark functions with various characteristics. The QLSA is applied to improve the design of the fuzzy logic controller (FLC) for controlling the speed response of the induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…LSA was first introduced in 2015 86 followed by its subsequent expansion 87 to the Quantum LSA (QLSA), which demonstrated enhanced performance. LSA was first introduced in 2015 86 followed by its subsequent expansion 87 to the Quantum LSA (QLSA), which demonstrated enhanced performance.…”
Section: Parameter Optimisation Via Application Of Qlsamentioning
confidence: 99%
See 1 more Smart Citation
“…LSA was first introduced in 2015 86 followed by its subsequent expansion 87 to the Quantum LSA (QLSA), which demonstrated enhanced performance. LSA was first introduced in 2015 86 followed by its subsequent expansion 87 to the Quantum LSA (QLSA), which demonstrated enhanced performance.…”
Section: Parameter Optimisation Via Application Of Qlsamentioning
confidence: 99%
“…The LSA is an optimisation technique inspired by the natural phenomenon of lightning caused by the propagation of negatively charged particles through space. LSA was first introduced in 2015 86 followed by its subsequent expansion 87 to the Quantum LSA (QLSA), which demonstrated enhanced performance. In this paper, 87 the operation of QLSA is described in detail, wherein it is revealed that the performance of QLSA is superior to that of algorithms based on the well-known particle swarm optimisation (PSO) approach and the backtracking search algorithm (BSA).…”
Section: Parameter Optimisation Via Application Of Qlsamentioning
confidence: 99%
“…A number of controllers are employed in the implementation of pulse width modulation (PWM) techniques, e.g., sine pulse width modulation (SPWM) and space vector pulse width modulation (SVPWM), for generating and regulating output of inverters. The SVPWM method is more complex compared to SPWM, especially for multilevel inverters [17,18]. Some of the controllers include analogue circuit controllers, microcomputers, digital circuit controllers, FPGA, and digital signal processors (DSPs) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Proposed in 2015, the lightening search algorithm (LSA) is a powerful and flexible optimization technique [25] that was inspired by the natural phenomenon of lightning. Some engineering optimization problems related to the parameter extraction of solar cell models [26], as well as modelling wind power [27], controlling voltage and frequency in a solar thermal power plant [28], and designing a speed controller for an induction motor drive [29], have been recently and successfully solved by applying the LSA method. The results obtained by the DLSA for the optimal placement of capacitors were compared with the results obtained by the genetic algorithm (GA), and the discrete harmony search algorithm (DHSA) at different wind speeds considering or disregarding harmonics.…”
Section: Introductionmentioning
confidence: 99%